PROPERTIES OF POLYCRYSTALLINE CADMIUM SULFIDE CDS FILMS DOPED WITH INDIUM ATOMS (Archive of Conferences, 2020)
In this work, CdS films were obtained by thermal evaporation on glass substrates with a SnO2 layer. In-doped CdS films were obtained by co-evaporation of CdS components by vacuum deposition, where the concentration of free charge carriers is 1017 cm-3 and the transparency of the films to the solar spectrum is preserved.